WEDDING GIFT-EXCHANGE AND ENDOWMENT AMONG THE PEOPLES OF DAGESTAN: TRADITIONS AND INNOVATIONS - Amirhanova, Aida Kiasbekovna; Bajramkulova, Aminat Ahmatovna (History, Archeology and Ethnography of the Caucasus, 2019)
The article aims to reveal the state of modern barter relations and endowing in wedding rituals of the peoples of Dagestan and to trace the variety of their transformation at different stages of a wedding.Wedding endowing and gift-exchange among Dagestanis today have similar features with traditional customs and rituals. However, over time, under the influence of ethnocultural and other processes, these rituals underwent certain transformations, adapting to the modern way of life of the people.Various exchange relations are an archaic tradition in the social life of any people, originating in ancient times. It is believed that the traditions of endowment and gift-sharing were invented to preserve existing or create new kindred and social relations within or between communities. Recently, however, wedding gift exchange has acquired utilitarian functions. Thus, many wedding gifts that were symbolic in the past are replaced today with money, the amount of which is increasing every year.Starting from the post-Soviet period, an increased interest and return of the peoples of Dagestan to their traditional customs and rites (including wedding ones) can be observed. However, their moral and ethical side remained in the past. To solve these issues, it is advised to facilitate the wedding and all its stages by gradually introducing reasonable ethical standards in modern rituals of endowment and gift-exchange, which allow regulating these rituals, streamlining the components of gift-giving and dowry, and the amount of them. It is necessary to reconsider the current traditional customs of gift-giving and endowing, to select and preserve the most important ones, which correspond to the modern lifestyle of the Dagestanis, discarding customs that are irrelevant and causing material damage to the family.
Keywords: peoples of Dagestan; gift-exchange; endowment; wedding; rituals; customs; traditions; innovations.